Impact of an Embedded Palliative Care Clinic on Healthcare Utilization for Patients With a New Thoracic Malignancy - Gast, Kelly C.; Benedict, Jason A.; Grogan, Madison; Janse, Sarah; Saphire, Maureen; Kumar, Pooja; Bertino, Erin M.; Agne, Julia L.; Presley, Carolyn J. (Frontiers in Oncology, 2022)
Introduction Palliative care is beneficial for patients with advanced lung cancer, but the optimal model of palliative care delivery is unknown. We investigated healthcare utilization before and after embedding a palliative care physician within a thoracic medical oncology “onco-pall” clinic. Methods This is a retrospective cross-sectional cohort study comparing healthcare outcomes in two cohorts: “pre-cohort” 12 months prior to and “post-cohort” 12-months after the onco-pall clinic start date. Patients were included if they had a new diagnosis of lung cancer and received care at The Ohio State University Thoracic Oncology Center, and resided in Franklin County or 6 adjacent counties. During the pre-cohort time period, access to palliative care was available at a stand-alone palliative care clinic. Palliative care intervention in both cohorts included symptom assessment and management, advance care planning, and goals of care discussion as appropriate. Outcomes evaluated included rates of emergency department (ED) visits, hospital admissions, 30-day readmissions, and intensive care unit (ICU) admissions. Estimates were calculated in rates per-person-years and with Poisson regression models. Results In total, 474 patients met criteria for analysis (214 patients included in the pre-cohort and 260 patients in the post-cohort). Among all patients, 52% were male and 48% were female with a median age of 65 years (range 31-92). Most patients had non-small cell lung cancer (NSCLC - 17% stage 1-2, 20% stage 3, 47% stage 4) and 16% had small cell lung cancer. The post-cohort was older [median age 66 years vs 63 years in the pre-cohort (p-value: < 0.01)]. The post-cohort had a 26% reduction in ED visits compared to the pre-cohort, controlling for age, race, marital status, sex, county, Charlson score at baseline, cancer type and stage (adjusted relative risk: aRR: 0.74, 95% CI: 0.58-0.94, p-value = 0.01). Although not statistically significant, there was a 29% decrease in ICU admissions (aRR: 0.71, 95% CI: 0.41-1.21, p-value = 0.21) and a 15% decrease in hospital admissions (aRR: 0.85, 95% CI: 0.70-1.03, p-value = 0.10). There was no difference in 30-day readmissions (aRR: 1.03, 95% CI: 0.73-1.45, p-value = 0.85). Conclusions Embedding palliative care clinics within medical oncology clinics may decrease healthcare utilization for patients with thoracic malignancies. Further evaluation of this model is warranted.